A Simple Strategy to Realize Super Stable Ferroelectric Capacitor via Interface Engineering. Issue 15 (7th April 2022) - Kim, Hyo‐Bae; Dae, Kyun Seong; Oh, Youkyoung; Lee, Seung‐Won; Lee, Yoseop; Ahn, Seung‐Eon; Jang, Jae Hyuck; Ahn, Ji‐Hoon
Abstract: Fluorite‐structure ferroelectric thin films have been extensively studied as promising candidates for next‐generation non‐volatile memory. However, these ferroelectric thin films have fatal issues such as the irregular formation of the ferroelectric phase, low cycling endurance, and wake‐up and fatigue during endurance cycling tests. These problems are reportedly caused by oxygen vacancies, which form due to the interface reaction between the thin films and bottom electrodes during deposition and the post‐annealing process. Therefore, in this work, the enhanced ferroelectric characteristics of Hf1‐x Zrx O2 thin films that control the oxygen vacancies in thin films through interfacial pretreatment are investigated. Interfacial treatment using an oxygen source can reduce oxygen vacancies and improve crystallinity through intentional oxidation of the bottom electrode. As a result, the remanent polarization value is increased by ≈1.6 times by applying the optimized pretreatment condition, and the measured 2 P r is a very high value of 73 µC cm −2 . Furthermore, it exhibits very stable ferroelectric properties without a wake‐up effect or significant fatigue, up to 10 8 cycles even under a severe electric field of 3.5 MV cm −1 . This simple strategy provides a new avenue to effectively improve the performance and cycling endurance of devices with ferroelectric thin films. Abstract : The superior stable ferroelectric characteristics of HZO‐TiN‐based capacitors are demonstrated via ozone pretreatment before thin film deposition. An excellent ferroelectric characteristic with a 2 P r of 73 µC cm −2 and constant P r value up to 10 8 cycles through ozone pretreatment is successfully achieved. This simple process represents a simple and novel strategy to effectively improve the performance and cycling endurance of devices using ferroelectric thin films.